CHARACTERISTICS AND BENEFITS OF BEE HONEY (REMUNOM, 2024)
Bee honey, contains natural sugars, stands out for its characteristics, its beauty in hives. Honey contains great nutritional and energetic value and is high in antioxidant content, the diversity of bees present in our ecosystem plays a fundamental role for us. The study addresses the importance of beekeeping, of bees for the ecosystem. The review also explored the potential, relevance of bees, production, and benefits in the food industry. Extracted honey is rich in amino acids, proteins and mineral salts, these properties bring several health benefits and are used in medicinal and immunization care products. In addition to all the benefits of honey in treating wounds or injuries in people with diabetes, it is anti-inflammatory, antioxidant and has antibacterial power and greatly helps with digestion. However, the relevance of the role of bees in maintaining the ecosystem and pollinating various plants and crops is highlighted, offering resources for local communities, small producers and for the commercialization of honey itself and products that use honey in the composition. In short, honey is a very valuable source of resources, with applications ranging from medicine and cooking.